Relationship between index-to-ring finger length ratio (2D:4D) and WOMAC osteoarthritis index in women with knee osteoarthritis - Shafuzain Ab Rahman; Nurul Fakhri Amir; Mohd Ariff Sharifudin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The difference in the index-to-ring finger length ratio (2D:4D) is associated with human behavior, physical capability, and risk of developing knee osteoarthritis in women. We aimed to determine the relationship between 2D:4D, Western Ontario and McMaster (WOMAC) osteoarthritis index, and body mass index (BMI) in women with mild to moderate knee osteoarthritis. A cross-sectional study was conducted on 118 women with Kellgren-Lawrence grade 2-3 knee osteoarthritis using the WOMAC questionnaire. The length of the index and ring fingers were measured using right-hand posterioanterior view plain radiographs. The participants were classified into three groups: type I (index finger longer than ring finger), type II (equal length), and type III (index finger shorter than ring finger). BMI was determined using standard measurements and calculations. There was no significant mean difference between the mean total WOMAC score and each of its components with the 2D:4D ratio. BMI correlated significantly with symptoms of knee osteoarthritis and the total WOMAC score (P<0.001). There was a significant relationship between the 2D:4D ratio and BMI (P=0.015). No relationship was found between the 2D:4D ratio and WOMAC score. However, there was a positive correlation between the WOMAC score and BMI. The 2D:4D ratio had a significant relationship with BMI.